Model Konseptual Teori Manajemen Pendidikan Islam Berbasis Filsafat: Kajian Ontologis, Epistemologis, dan Aksiologis - Yuli Supodo; Abd. Mui_N (Jurnal Pendidikan Educandum, 2026)
This study develops a conceptual model of Islamic education management theory from a philosophical perspective, emphasizing ontological, epistemological, and axiological dimensions rooted in revelation, reason, and Islamic values. Employing qualitative library research with descriptive-reflective analysis, primary sources (Quran, Sunnah) and secondary literature from Islamic philosophers (e.g., Al-Attas) are synthesized to explore philosophy's role in strengthening theoretical foundations. Findings highlight philosophy as essential for integrating monotheism (tauhid), justice, trustworthiness (amanah), and public welfare (maslahah) into holistic management paradigms. The proposed model distinguishes itself by embedding spiritual-moral dimensions in contemporary management theory, offering theoretical enrichment and practical guidance for Islamic educational leaders. Implications include a new referential framework for research and policy in sustainable Islamic education.